Urgensi Pendidikan Shalat pada Anak dalam Keluarga; Studi Analisis H?adîth tentang Hukuman bagi Anak Tidak Shalat - Ali Mustofa; Ishak Ishak (Muróbbî: Jurnal Ilmu Pendidikan, 2017)
The family is the primary educational environment for children. In Islam, education must make people who devote themselves to worship God. And worship was first required is prayer because prayer is pillar of religion. Inside are virtue and wisdom to who do it well as threat to the left. Little kid is not obligated to pray, but the family (parents) have a responsibility and obligation to educate their children, to invite children to pray after a seven year old child, and hit if not want to do the prayer at the age of ten years. But before hitting, parents also need to have educating prayer before age ten. Although the children were not required to prayers, but parents should always pay attention and control the execution of a child prayers. Education prayers in these children very well have implications for the psychological, physical, and social child. Moreover, if the study is successful, the prayer will become a necessity. So the psychiatric, physical, and social child always running stable until in adulthood.